Enhancing the development role and impact of UNCTAD : report (UN New YorkUS, 2006)
Recommends the strategies UNCTAD needs to follow in order to fulfil its development mission and mandates as contained in the Bankok Plan of Action and the Sao Paulo Consensus.
Keywords: UNCTAD